2021
DOI: 10.1177/14705958211051551
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on leadership development in post-Soviet Eurasia

Abstract: Young people throughout Eurasia are looking for leadership that is different from what preceding generations experienced in the Soviet era and many people are still accustomed to, namely a less top-down authoritarian style by a solo leader reflecting the outdated ‘Great Man’ model of ‘strong’ leadership and for a more collaborative, participative style with more dispersed leadership. This implies the need for a significant cultural change. Leadership development programmes now need to refocus their philosophy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The results of the analysis of descriptions of performance found that the performance of Kesdam XII members in Tanjungpura Pontianak was able to complete work on time in accordance with the targets and provisions in force. (Gill & Negrov, 2021) states that: "Leadership style is the way a leader influences the behavior of subordinates which aims to encourage work passion, job satisfaction and high employee productivity, in order to achieve maximum organizational goals." According to respondents' perceptions, it was found that members' leadership styles can influence performance.…”
Section: B Relationship Between Research Variablesmentioning
confidence: 99%
“…The results of the analysis of descriptions of performance found that the performance of Kesdam XII members in Tanjungpura Pontianak was able to complete work on time in accordance with the targets and provisions in force. (Gill & Negrov, 2021) states that: "Leadership style is the way a leader influences the behavior of subordinates which aims to encourage work passion, job satisfaction and high employee productivity, in order to achieve maximum organizational goals." According to respondents' perceptions, it was found that members' leadership styles can influence performance.…”
Section: B Relationship Between Research Variablesmentioning
confidence: 99%